Szanse i zagrożenia dla sektora banków komercyjnych w Polsce oraz perspektywy jego rozwoju : część 2 - Swacha-Lech, Magdalena (Threats and Opportunities for the Bank Sector in Poland and Its Development Perespectives, 2006)
The aim of the article that follows is the attempt to identify the main directions of Polish banking system development, which have been presented as the consequence of the phenomena taking place in bank environment. Among the factors which influence bank sector development one can distinguish 1) the forming of new legislation regulating bank market development, 2) economic environment changes and client behaviour and preference changes. 3) the growth of foreign banks competition as well as of other home and foreign financial market institutions, 4) general trends in the world economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 196-214